Deepening the customs union relationship in the Organization of Eastern Caribbean States - Clarke, Silbourne St. A ([s.n] [S.l], 1987)
Reviews provisions in the Eastern Common Market (ECM) Agreement which facilitate customs union operation, and gives overview of their general application. Examines the ECCM - CARICOM relationship focusing on aspects that affect the intra - OECS customs union relationship. Reviews the nature of a number of customs union concepts and accepted criteria applying to them. Discusses issues and options in deepening the customs union relationship within the OECS.